The Pediatric Knee: Diagnosis and Management of Ligament Injuries - Wegmann, Helmut; Tschauner, Sebastian; Singer, Georg; Marterer, Robert; Eberl, Robert; Sorantin, Erich (Seminars in Musculoskeletal Radiology, 2014)
In the last few decades, sports injuries in pediatric and adolescent athletes have increased dramatically, with ∼ 38 million young athletes participating in organized sports annually in the United States. Starting at the age of 2 years, an increase of the incidence of knee injuries until adulthood with a peak at 6 and at 13 years of age has been observed. Due to a physiologic laxity of the ligaments, ligament injuries are uncommon in these patients, but they are getting more frequent. In the growing knee, open physis are the points of minor resistance. Therefore apophyseal injuries of the pediatric knee are more common. Diagnostics and treatment of ligament injuries of the pediatric and adolescent knees are challenging. This article presents an overview of ligament injuries in the pediatric and adolescent knee, their diagnostic work-up, and their treatment in the growing patient.
Keywords: pediatric; adolescent; knee; ligament injury; diagnostic